Periorbital squamous cell carcinoma with orbital invasion - Jain, Navneet; Pathak, Priyank (International Surgery Journal, 2016)
Periocular squamous cell carcinoma is an aggressive tumor with incidence for eyelid SCC has been reported to be between 0.09 and 2.42 cases per 100 000 population. SCC is the second most common eyelid malignancy, accounting less than 5% of malignant eyelid neoplasms. Orbital invasion is a serious complication of aggressive or neglected lesions, which has been reported to occur in 2.5% of all eyelid basal and squamous cell carcinomas. The aim of our study is to report a case of a 58-year male with periorbital squamous cell carcinoma referred to our clinic because of non-healing ulcer over the left frontal region. This case study reports a complication of orbital invasion with emphasis on the review of literature.